Context-aware inference in ubiquitous residential environments - Lee, J.; Lee, H.; Kim, M.; Wang, Xiangyu; Love, Peter (ELSEVIER, 2014)
Residential ubiquitous computing environments have focused on interconnecting environmental controls using a home network and the management of sensor data rather than a context-aware inference. Building upon previous research, this paper proposes a novel sensor-based context-aware system with a focus on three inference processes: rule, inference and pattern driven. Using pattern data derived from five families for a working week and establishing rules and inferences, the proposed context-aware system is demonstrated using electrical lighting as an example. The processes to develop an intelligent house are described so as to ameliorate personalized services in response to inhabitants’ needs.